Evaluation of Latex Modified Asphalt Mixture with Recycled Concrete Aggregate (RCA) - Arshad, Ahmad Kamil; Shaffie, Ekarizan; Mohamad Kamal, Mohd Izzat Asyraf; Kamaluddin, Noor Azreena; Hashim, Wardati (International Journal of Sustainable Construction Engineering and Technology, 2024)
Natural rubber latex (NRL) is currently added into bitumen to improve the performance of asphalt concrete m??tures. However, the addition of NRL increased the cost of production and road authorities are generally reluctant to use a higher cost product albeit with better performance. The use of RCA such as from building demolitions can offset this increase in cost in the use of NRL modified bitumen. However, there is a need to ensure that the quality of the asphaltic concrete is not compromised by the addition of RCA. This paper details a study to evaluate the use of NRL m?d?f??d ???h?lt bitumen together with 50 percent RCA on the performance of hot m?? ???h?lt. Commercially produced bitumen m?d?f??d with NRL was used for the ???h?lt m??es. Dense ???h?ltic concrete AC14 specimens were then prepared using the m?d?f??d bitumen together with the addition of 50 percent RCA by weight replacing the virgin aggregate. Performance tests were then carried out on the samples which include moisture susceptibility test, r???l??nt modulus test, ?nd dynamic creep test. The results revealed that the use of NRL together with 50 percent RCA to dense ???h?ltic concrete m??es gave comparable performance to conventional dense asphalt concrete mixes. It can be concluded that the use of NRL modified bitumen together with 50 percent RCA can provide a cost-effective solution to increase the performance of hot mix asphalt.